2018
DOI: 10.26434/chemrxiv.6789326
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Chemical Accuracy in Modeling Halide Ion Hydration from Many-Body Representations

Abstract: <div> <div> <div> <p>Despite the key role that ionic solutions play in several natural and industrial processes, a unified, molecular-level understanding of how ions affect the structure and dynamics of water across different phases remains elusive. In this context, computer simulations can provide new insights that are difficult, if not impossible, to obtain by other means. However, the predictive power of a computer simulation directly depends on the level of “realism” tha… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 118 publications
2
17
0
Order By: Relevance
“…Many-body reference energies, calculated using the SAMBA approach, 122 are listed in Tables 1 and 2 we found to consistently provide good agreement with coupled-cluster reference energies for various aqueous and non-aqueous systems. 83,85,86,96,97,128,129 As expected from the correlation plots shown in Fig. 2, the TTM-nrg PEF displays significantly larger deviations from the ref- Table 2 for individual terms of the MBE in Eq.1 calculated at the ωB97M-V, TTM-nrg, and MB-nrg levels of theory for the same (CH 4 ) m (H 2 O) n clusters, with m + n ≤ 5, shown in Fig.3.…”
Section: Assessment Of Ttm-nrg and Mb-nrg Accuracysupporting
confidence: 55%
See 1 more Smart Citation
“…Many-body reference energies, calculated using the SAMBA approach, 122 are listed in Tables 1 and 2 we found to consistently provide good agreement with coupled-cluster reference energies for various aqueous and non-aqueous systems. 83,85,86,96,97,128,129 As expected from the correlation plots shown in Fig. 2, the TTM-nrg PEF displays significantly larger deviations from the ref- Table 2 for individual terms of the MBE in Eq.1 calculated at the ωB97M-V, TTM-nrg, and MB-nrg levels of theory for the same (CH 4 ) m (H 2 O) n clusters, with m + n ≤ 5, shown in Fig.3.…”
Section: Assessment Of Ttm-nrg and Mb-nrg Accuracysupporting
confidence: 55%
“…1 to develop TTM-nrg and MB-nrg PEFs for halide-water, 82,83 alkali-metal ion-water, 84,85 and carbon dioxide-water systems, 86 which have been employed in computer simulations of various aqueous systems. [94][95][96][97][98][99][100][101] While both TTM-nrg and MB-nrg PEFs rely on MB-pol to describe water-water interactions, they differ in the functional forms adopted to represent solute distortions and solute-water interactions. In the TTM-nrg PEF, the CH 4 1B term is represented by a functional form similar to those used in common force fields, which is expressed in Eq.…”
Section: Ttm-nrg and Mb-nrg Functional Formsmentioning
confidence: 99%
“…It should be noted that our previous analyses showed that, among the existing functionals, ωB97M-V consistently provides the closer agreement with CCSD(T) reference data for molecular interactions in aqueous systems. 69,71,81,82,111 As expected from the analysis of the correlation plots in Fig. 2 A direct probe of the multidimensional 2B energy landscape is provided by the second virial coefficient,…”
Section: Many-body Decompositionmentioning
confidence: 67%
“…1 can be correctly represented in terms of classical many-body polarization as described in Section 2.1. In this context, it should be noted that previous studies of manybody effects in aqueous systems indicated that an explicit representation of 3B energies is necessary to guarantee an accurate description of structural, thermodynamic, dynamical and spectroscopic properties of water 75,[109][110][111] as well as halide-water 69,79,[81][82][83][84][85] and alkali-metal ion-water 71,80,86 interactions in the gas phase and in solution. In particular, it was found that significant error cancellation between different terms of the MBE affects the performance of common force fields and DFT models for water.…”
Section: Many-body Decompositionmentioning
confidence: 99%
“…Many of these models, while yielding very accurate results, are computationally expensive. For example, MB-pol is regarded as one of the most accurate models, but it is ∼50 times more computationally expensive than AMOEBA, and has not yet been used for simulations beyond water 133 136 and water-halide (using MB-nrg which is based on MB-pol 137 ) systems. For further information about advanced water models, including parametrization and machine learning methods, the reader is directed to the recent review papers by Cisneros et al.…”
Section: Water Models In Molecular Dynamics Simulationsmentioning
confidence: 99%